Rencana Pembangunan Kawasan Industri terhadap Perkembangan Nilai Tanah: Studi Kasus di Kabupaten Cilacap Tahun 2023 - Ladya Zhafirah; Setiowati; Sudibyanung (Kadaster: Journal of Land Information Technology, 2023)
ABSTRACT The availability of suitable land is a crucial factor in determining the success of regional development. In 2022, as part of their regional economic development initiative, the Cilacap Regional Company planned to establish the Cilacap Industrial Zone, leading to significant changes in land use and a potential impact on land prices in the surrounding area. Regions undergoing high development activities tend to experience an increase in land value. Consequently, there exists the possibility of potential changes and developments in land value around the Cilacap Industrial Zone. This study aims to analyze the extent of increase and the pattern of land value distribution in locations surrounding the Cilacap Industrial Zone. The research method employed was a survey approach with a quantitative methodology. The findings reveal that the planned development of the Cilacap Industrial Zone resulted in an increase in land value, particularly in agricultural lands, with an average increase of Rp 441.744/m2. The distribution pattern of land value in the vicinity of the Cilacap Industrial Zone can be categorized into 11 groups, with percentage increases ranging from below 100% to above 400%. Keywords: land value, Cilacap Industrial Zone, distribution pattern, industry.